Correlation between Anterior Crowding and Attrition in Young Adults - P.S, Samyuktha; kumar Pandurangan, Kiran; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Dental crowding is associated with a difference between the existing space and the necessary space of the teeth on the arches; this is a possible symptom of skeletal malocclusions. The clinical forms of crowding are mild, moderate, or severe depending on their manifestation. Attrition is described as the condition resulting mainly from tooth-to-tooth contact without any foreign substance intervention. It is also described as the physiological wearing off of teeth. Aim: To evaluate if there is any correlation between anterior crowding and attrition in young adults. Materials and Method: A total of 100 individuals were assessed for crowding and attrited teeth. To assess the status of crowding and attrition, clinical examinations along with intraoral photographs were taken. The data obtained was tabulated, and using the SPSS software, a nonparametric correlation coefficient was calculated using Spearman’s method. Results: In the 100 anterior crowded individuals that were studied, 63 showed attrited teeth and 37 did not show attrited teeth. The Spearman correlation coefficient p value of 0.46 was obtained. Conclusion: The study revealed a positive correlation between anterior crowded teeth and attrition in the population studied.